Approach to the Treatment of Cows with the Diseases of the Distal Part of the Extremities - I. Mikhailova, Irina; R. Leshchenko, Tatyana; A. Evglevsky, Alexei; P. Evglevskaya, Elena; N. Mikhailova, Olesya; Yu. Finageiv, Evgeny (International Journal of Psychosocial Rehabilitation, 2020)
Currently, farming in Russia is focused on the upscale production of meat and dairy products. However, the high rate of non-infectious diseases in animals prevents the fulfillment of the state program of import substitution. Thus, there is a great number of cows with hoof diseases registered in the farm complexes of Rostov Oblast. The analysis of the origins of the pathology of distal parts of extremities showed that contributing factors to these diseases are metabolism disorders, animal immune status failure, and violation of zoo hygienic norms in the husbandry. Considering all the available data, the authors proposed a complex approach to the treatment of cows with purulonecrotic lesions of the distal parts of their extremities. The approach combines targeting the local abnormal focus and systemic effect. The authors evaluated the effect and implemented in practice an energy metabolism-enhancing composition that included succinic acid, beetroot molasses, and potassium chloride. Application of this composition allowed for the reparation of immune metabolic processes in cows, improvement in tissue trophic in the pathologic lesion, and acceleration of animals’ recovery.